Production of Inflammatory Markers (IL-8, IL-4and IFN- )and risk of Ischemic Hart Diseases. - AL-Najy, Mahdi H.; AL-Joofy, kbal K.; AL-Marayati, Amaal N. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Ischemic heart diseases (I.H.D) become the most common cause of sudden death, and is also the most common reason for death of man and women over 20 years of age in the world. Many Factors Play a role in pathogenesis of I.H.D. among those could be Immune – inflammatory markers which may lead to development of this disease.The present study was conducted to obtain more clarification about the impact of some immuno – inflammatory markers (IL- 8 , IL- 4 and IFN- Ճ) on the Clinical expression of heart disease among Iraqi patients .Patients and methods: Hundred Iraqi patient with I.H.D. (80 male and 20 female) ages ranged between 20 to 80 year were involved in this study, include 4 subgroups: 17 with heart failure (H. F) ; 26 with myocardial infraction (M.I) ; 12 with stable angina (S.A) and 45 with unstable angina (U.A) who attending the Iraqi Center for Heart Disease and Baghdad Hospital from December 2006 to march 2007 . For quantitative estimation of serum levels of IL- 8, IL- 4 and IFN- Ճ by Enzyme Amplified Sensitivity Immuno Assay (EASIA) technique for both patients and healthy control groups.Results: Significant increased (P< 0.05) in the serum level of interleukin – 8 in all patient subgroups: H.F., M.I, S.A and U. A. respectively Compared with control group, also all patient subgroups: H. F., M. I, S.A and U. A. Consequently revealed Significant increased (P< 0.05) in the interleukin – 4 Concentration compared with control group. More over, highly Significant increased (P< 0.01) in the interferon – Ճ concentration in the patients Subgroups: H. F, M. I, S.A and U. A respectively compared with control group.Conclusion: Elevated level of inflammatory Markers (IL- 8, IL- 4 and IFN – Ճ) in all patients of I.H.D reflects the importance immuno – inflammatory elements as risk factor in the pathogenesis of Heart Disease.